Mathematical simulation and optimization of cutting modes in turning of titanium alloy workpieces; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Bogoljubova (Bogolyubova) M. N. Mariya Nikitichna; Afonasov A. I. Aleksey Ivanovich; Kozlov V. N. Victor Nikolayevich; Sumtsova O. V. Olga Vitalievna (Numerical Simulation of Applied Problems, 2016)
Title screen